Entrepreneurial Attitude and Intention of ABM Senior High School Learners - Cano, Junar S.; Caro , Haelen Kie; Chioco, Andreana Paulene; Fusingan, Roy Angelo; Matulac, Katrenna Andrea; Sabio , Zillah Jayne; Gaygay, Carlos; Pat-i, Ryzel Vonn D. (Future Science / FSH-PH Publications, 2022)
Due to the global health crisis, many people lost their jobs or had to accept lower compensation. To mitigate the economic constraints caused by the pandemic, people pursued entrepreneurship to help meet their basic needs. However, to become successful in the field of entrepreneurship, one must possess a high level of entrepreneurial attitude and intention. Although a considerable study had been conducted to assess the level of entrepreneurial attitude and intention, its Senior High School (SHS) level implementation had only received far less attention. Likewise, a dearth of literature assesses the level of entrepreneurial attitude and intention among Accountancy, Business and Management (ABM) SHS learners. Hence, this study was conducted to determine the level of entrepreneurial attitude and intentions of the Grade 12 ABM SHS learners. The study utilized a descriptive correlational research design. A total of 58 ABM SHS learners from NDMU-IBED, Philippines, were purposively chosen as the respondents of the study. Results revealed that the learners have a high entrepreneurial attitude and intention. Further, Spearman's correlation revealed that there was a statistically significant moderate positive correlation (p<0.05) between the two variables. These indicate that learners have a high attitude toward becoming an entrepreneur and desire to put up or start their businesses. More so, ABM SHS learners' entrepreneurial attitude can be used as a predictor of their entrepreneurial intention.